ANALISIS MODEL BISNIS UMKM KULINER SATE TAICHAN "TITIK BERKALA" DENGAN PENDEKATAN BUSINESS MODEL CANVAS DAN ANALISIS SWOT - Al Anshari; Hikmah Dzil Hijjah; Arsalan Bintang Romadi (Media Resonansi Pengabdian Masyarakat, 2025)
This study analyzes the business model and development strategy of the culinary MSME "TITIK BERKALA" owned by college alumni. With a case study and qualitative approach, Business Model Canvas and SWOT analysis were used. Data were obtained from observations, interviews, and documents. The results showed that the strength of the business lies in the quality sate taichan menu, affordable prices, and strategic location. Weaknesses include the use of digital technology, financial records, and loyalty programs that are not yet optimal. The study recommends five strategies: digital marketing, menu diversification, management improvement, loyalty programs, and business expansion. This study provides a practical reference for the development of MSMEs by young entrepreneurs and a theoretical contribution to the study of culinary MSME business models in Indonesia.Keywords: Culinary MSMEs, Sate Taichan, Business Model Canvas, SWOT Analysis, Business Model